O que se passa nos processos formativos? O labor de um êthos na produção de si. - César, Janaína Mariano (2013)
This work discusses the formative experience, stating it in a broader perspective, which includes the official formation, schooled, and expands it in possibilities. It invites to think formation as an experience of subjectivity, of building oneself and the world. Therefore it considers that the construction and modification of what we are, have as surface of elaboration the everyday practices. Having Foucault as intercessor and his use of Greek and Roman literature, it accompanies in the history of Western thinking the production of a formation, whose relationship with truth would lie in the principle of self-knowledge. In it, the production of knowledge conditiones itself to already available truths, only waiting for discovery, through the appropriate tools. In that formative proposal, the subject would not be asked any ethic work of transformation for the access to the experience of knowing. It states, consequently, a formative policy combined to the principle of self-care, which even surpassed, coexists in our practices. In this other policy, of an ontology of the present, echoes the voices of Maturana and Varela, Deleuze and Guattari, Don Juan, Itto Ogami, Larrosa, Foucault, Seneca, Socrates and many other teachers who invest in it . It invites the statement of that route, demanding about a hard work of self-change. Its effects would not be in the accumulation of a monumental and decorative knowledge, but in the unlearning of habits and behaviours that creates obstacles to the operation of freedom in the action-thinking. Such formative policy presupposes the construction of devices located in everyday life, that mobilize and give support for the work on oneself. This direction will motion the group’s device with the involvement of undergraduate course students, built as an interventionresearch plan, that feeds this work. In this course, the universityschool is experienced, not anymore as an absolute formative center, being a life the excellence of the formative plan, but as a network of possible practices of a work on us. It suffers re-arrengements in its destinations, concluding itself as a way of ethical and political elaboration of the work of our existence.